2018
DOI: 10.1002/adfm.201704598
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle‐Based Fluoroionophore for Analysis of Potassium Ion Dynamics in 3D Tissue Models and In Vivo

Abstract: The imaging of real-time fluxes of K+ ions in live cell with high dynamic range (5-150 mM) is of paramount importance for neuroscience and physiology of the gastrointestinal tract, kidney and other tissues. In particular, the research on high-performance deep-red fluorescent nanoparticle-based biosensors is highly anticipated. We found that BODIPY-based FI3 K+-sensitive fluoroionophore encapsulated in cationic polymer RL100 nanoparticles displays unusually strong efficiency in staining of broad spectrum of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 61 publications
(64 reference statements)
0
30
0
Order By: Relevance
“…Because fluorescence is highly conformation dependent, additional proteins linked to GCaMP2 may compromise the structure of GCaMP2, which leads to the loss of discriminated fluorescent lifetime when detecting Ca 2+ in intestinal organoids (O'Donnell et al, ). To make the fluorescent dyes more stable, Müller et al () encapsulated a boron‐dipyrromethene‐based K + ‐sensitive fluoroionophore, FI3 into cationic polymer RL100 nanoparticles to image the real‐time fluxes of K + in intestinal organoids ( Figure d ) . Via a series of experiments, they found that (a) the nano‐coated FI3 has a higher efficiency of intracellular transportation than the free one.…”
Section: Live‐imaging Biosensors For Detection Of Intestinal Organoidsmentioning
confidence: 99%
“…Because fluorescence is highly conformation dependent, additional proteins linked to GCaMP2 may compromise the structure of GCaMP2, which leads to the loss of discriminated fluorescent lifetime when detecting Ca 2+ in intestinal organoids (O'Donnell et al, ). To make the fluorescent dyes more stable, Müller et al () encapsulated a boron‐dipyrromethene‐based K + ‐sensitive fluoroionophore, FI3 into cationic polymer RL100 nanoparticles to image the real‐time fluxes of K + in intestinal organoids ( Figure d ) . Via a series of experiments, they found that (a) the nano‐coated FI3 has a higher efficiency of intracellular transportation than the free one.…”
Section: Live‐imaging Biosensors For Detection Of Intestinal Organoidsmentioning
confidence: 99%
“…Potentially, NAD(P)H-FLIM and O2-PLIM methods could be multiplexed with each other, and with additional measurement assays, such as labeling of other cell types (genetically or via fluorescent tracers), labeling cell proliferation 29 and measurement of mitochondrial membrane potential 18 . Curiously, the majority of commercially available FLIM-PLIM microscopes have limited microsecond PLIM measurement range 33 , many high-performance O2 probes are not suitable for twophoton excitation 37 , cannot stain organoids or possess other drawbacks 45,46 . An important feature of the microscopy approaches presented here is that they can be performed with live samples and indeed are compatible with downstream assays, such as tissue clearing with light sheet microscopy, coherent anti-Stokes Raman spectroscopy and others 15,22 .…”
Section: Overall Comparison Of Methodologiesmentioning
confidence: 99%
“…Nanoparticle-based fluoroionophore for analysis of potassium ion dynamics in 3D tissue models and in vivo (Muller et al [38])…”
Section: Title and Authors Microscope Applicationmentioning
confidence: 99%
“…Most studies used rodent models, except for Cozzolino et al [39], and Verdugo et al [47], who both used zebrafish models, while Kerekes et al [40], Chia et al [66], and Hakvoort et al [21] examined human brain tissue. Twenty-three studies used mouse models [31][32][33][34]36,37,41,42,45,46,48,49,[53][54][55]58,60,61,63,64], seven used rat models [50][51][52]59,62,65,66], three used both rat and mouse models [29,35,38], and one used a guinea pig model [56]. In addition, fourteen of the studies applied 2PI to visualize ex vivo cells in brain slices [21,29,34,35,38,[40][41][42]45,48,[50]…”
Section: Study Characteristicsmentioning
confidence: 99%